2021
DOI: 10.1002/ejsp.2748
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the intergroup sensitivity effect: Defending the ingroup or enforcing general norms?

Abstract: Group members reject threatening outgroup criticism compared to the same criticism from the ingroup (intergroup sensitivity effect [ISE]). Uninvolved bystanders (i.e., members of third groups) also view intergroup criticism as inappropriate. Classic ISE studies were largely underpowered, used inconsequential self-reports, and no study has observed behavioural responses of bystanders versus ingroup members. We argued that norms may elicit self-report responses but only social identity concerns of highly identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 61 publications
9
49
0
Order By: Relevance
“…The desecration of a symbol, whether of the ingroup or of the outgroup, can be perceived as an act of deviance when it is committed by a member of the ingroup. Desecration of an outgroup symbol violates the norm of non-aggression of other groups (Crandall et al, 2002;Thürmer & McCrea, 2021) and may cause a threat to social identity, as shown by our results reporting a greater perceived threat to the group's image when an outgroup (vs. ingroup) flag is burnt. However, our studies confirm that the desecration of an ingroup symbol can also be threatening to certain individuals, who place particular emphasis on the norm of loyalty to the nation: the most blindly patriotic people.…”
Section: Symbol Desecration and Blind Patriotismmentioning
confidence: 65%
See 1 more Smart Citation
“…The desecration of a symbol, whether of the ingroup or of the outgroup, can be perceived as an act of deviance when it is committed by a member of the ingroup. Desecration of an outgroup symbol violates the norm of non-aggression of other groups (Crandall et al, 2002;Thürmer & McCrea, 2021) and may cause a threat to social identity, as shown by our results reporting a greater perceived threat to the group's image when an outgroup (vs. ingroup) flag is burnt. However, our studies confirm that the desecration of an ingroup symbol can also be threatening to certain individuals, who place particular emphasis on the norm of loyalty to the nation: the most blindly patriotic people.…”
Section: Symbol Desecration and Blind Patriotismmentioning
confidence: 65%
“…Desecrating the national symbols of the ingroup is seen as immoral (Haidt et al, 1993) and as an act of disloyalty and disrespect toward the national group (Graham et al, 2011;Welch, 2000). On the other hand, desecrating the symbol of an outgroup violates the norm of non-aggression toward other groups (Crandall et al, 2002;Thürmer & McCrea, 2021). Thus, desecration of both an ingroup and an outgroup symbol can be considered an act of deviance, varying in degree depending on the emphasis placed on either the norm of loyalty or of non-aggression of outgroups, respectively.…”
Section: Ingroup Symbol Desecration: a Threat To Social Identity Among Blind Patriotsmentioning
confidence: 99%
“…Moreover, Thürmer et al (2019) observed that group members spent their time counter-arguing outgroup criticism instead of completing their individual work, even when their individual work was intrinsically rewarding (i.e., evaluating funny video clips). A recent preregistered, large-scale replication confirmed the behavioral ISE (Thürmer & McCrea, 2021a). Apparently, outgroup criticism motivates people to engage in costly defensive behaviors.…”
Section: Expressed Outgroup Identity Motivates Collective Defensivenessmentioning
confidence: 89%
“…As recommended by Funder et al (2014), we assumed a small-to-medium effect of f = .15. Such an effect also provides a conservative estimate of the self-report effects observed in similar past ISE research (Thürmer & McCrea, 2018, 2021a. The analysis resulted in a minimum sample size of N = 600 for the main effect; to account for potential dropouts (see below), we aimed to recruit at least 700 participants.…”
Section: Methods Participants and Designmentioning
confidence: 99%
“…Desecrating the national symbols of the ingroup is seen as immoral (Haidt et al, 1993) and as an act of disloyalty and disrespect toward the national group (Graham et al, 2011;Welch, 2000). On the other hand, desecrating the symbol of an outgroup violates the norm of non-aggression toward other groups (Crandall et al, 2002;Thürmer & McCrea, 2021). Thus, desecration of both an ingroup and an outgroup symbol can be considered an act of deviance, varying in degree depending on the emphasis placed on either the norm of loyalty or of nonaggression of outgroups, respectively.…”
Section: Ingroup Symbol Desecration: a Threat To Social Identity Among Blind Patriotsmentioning
confidence: 99%